2015
DOI: 10.1002/dta.1898
|View full text |Cite
|
Sign up to set email alerts
|

Coronary thrombosis and marijuana smoking: a case report and narrative review of the literature

Abstract: We encountered evidence of myocardial infarction due to coronary thrombosis in an autopsy of an occasional marijuana smoker. These findings prompted us to perform a narrative review of the literature to determine when post-mortem toxicological tests may support a temporal relationship between marijuana smoking and cardiovascular disease. Toxicological examination showed the presence of Δ-9-tetrahydrocannabinol, its main metabolite and cannabinol in blood and urine. Quali-quantitative analysis revealed that Δ-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 91 publications
(137 reference statements)
3
12
0
Order By: Relevance
“…Multiple case reports have linked marijuana to thrombus formation, leading to acute myocardial infarction in young adults [15,[37][38][39][40][41]. The pro-coagulant effect of marijuana is attributed to the presence of CB1R and CB2R on human platelets.…”
Section: Effect Of Marijuana On Thrombosismentioning
confidence: 99%
“…Multiple case reports have linked marijuana to thrombus formation, leading to acute myocardial infarction in young adults [15,[37][38][39][40][41]. The pro-coagulant effect of marijuana is attributed to the presence of CB1R and CB2R on human platelets.…”
Section: Effect Of Marijuana On Thrombosismentioning
confidence: 99%
“…▪ Significant cannabis exposure in contrast to many previously published studies. ▪ Study limitations included that only 11 cannabis-only patients could be identified of the 125 cannabis-exposed patients. ▪ Significant coefficient of variation was found with the biomarker of cardiovascular-organismal age employed; use of an alternative parameter such as epigenetic age based on DNA methylation would allow more refined and detailed studies in smaller patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…Marchetti et al [53] attempted to find evidence of MI due to coronary thrombosis in an autopsy of an occasional cannabis smoker. They performed a narrative review of the literature to establish when postmortem toxicological tests may support a temporal association between cannabis smoking and CVD.…”
Section: Unknowns Associated With Cannabis Consumptionmentioning
confidence: 99%